Limitations of arterial partial pressure of oxygen to fraction of inspired oxygen ratio for the evaluation of donor lung function. Issue 11 (18th July 2022) - Fumagalli, Jacopo; Colombo, Sebastiano Maria; Scaravilli, Vittorio; Gori, Francesca; Pesenti, Antonio; Zanella, Alberto; Grasselli, Giacomo
Abstract: Background: Evaluation of donor lung function relies on the arterial oxygen partial pressure to inspired oxygen fraction ratio (PaO2 /FiO2 ) measurement. Hemodynamic, metabolic derangements, and therapeutic intervention occurring during brain dead observation may influence the evaluation of gas exchange. Methods: We performed a mathematical analysis to explore the influence of the extrapulmonary determinants on the interpretation of PaO2 /FiO2 in the brain‐dead donor and during Ex‐Vivo Lung Perfusion (EVLP). Results: High FiO2 and increased mixed venous oxygen saturation, caused by increased delivery and reduced consumption of oxygen, raise the PaO2 /FiO2 despite substantial intrapulmonary shunt. Anemia does not modify the PaO2 /FiO2 —intrapulmonary shunt relationship. During EVLP, the reduced artero‐venous difference in oxygen content increases the PaO2 /FiO2 without this corresponding to an optimal graft function, while the reduced perfusate oxygen‐carrying capacity linearizes the PaO2 /FiO2 —intrapulmonary shunt relationship. Conclusions: Adopting PaO2 /FiO2 to evaluate graft suitability for transplantation should account for extrapulmonary factors affecting its interpretation. Abstract :